1993
DOI: 10.1002/j.2161-0045.1993.tb00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Commonality and Difference: The Key to Career Counseling With Lesbian Women and Gay Men

Abstract: Miller -Tiedeman (1987) coined the term lifecareer to underscore the interrelatedness of life and career, that planning for career must flow from the total life experience of the individual. Nowhere is such a concept more important than in doing career work with clients who are part of a social or cultural group that faces oppression within the larger society. In addition to the myriad of factors seen in any client, the life context of oppressed peoples includes factors related to their specific culture and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…These investigators found that the period in which lesbians consolidated their lesbian identities did delay or disrupt the career development process. Such negative repercussions may be transitory, however, as an individual learns to manage stigma and to create affirmative environments through the successful progression of sexual identity development (Croteau & Hedstrom, 1993;Fassinger, 1995;Hetherington & Orzek, 1989).…”
Section: Sexual Identity Developmentmentioning
confidence: 99%
“…These investigators found that the period in which lesbians consolidated their lesbian identities did delay or disrupt the career development process. Such negative repercussions may be transitory, however, as an individual learns to manage stigma and to create affirmative environments through the successful progression of sexual identity development (Croteau & Hedstrom, 1993;Fassinger, 1995;Hetherington & Orzek, 1989).…”
Section: Sexual Identity Developmentmentioning
confidence: 99%
“…Issues to address in such a discussion include the how-tos (Croteau & Hedstrom, 1993;Pope & Schecter, 1992) and the whys associated with deciding to come out (Brown, 1975;Pope, 1995c). Professional counselors can help their clients consider the advantages and disadvantages of coming out in the workplace or school (Adams, 1997;Belz, 1993;Brown, 1975;Croteau & Hedstrom, 1993;Elliott, 1993;Morgan & Brown, 1991;Morrow, 1997;Pope, Rodriguez, & Chang, 1992;Pope & Schecter, 1992;Savin-Williams, 1993). They can provide clients with opportunities for behavioral rehearsals that are directed toward developing and training strategies for informing others.…”
Section: Client-focused Interventionsmentioning
confidence: 99%
“…Engels ( I 994) postulated that the career development process addresses an individual's needs and goals that are associated with different stages of life; the focus and importance of career decision making and occupational choice may change over the years. In addition to environmental influences that affect both heterosexual women and lesbians, lesbians have the additional variable of sexual orientation, which makes it imperative to consider the impact of being lesbian and the prejudice against lesbian and gay individuals when making choices in work and career (Croteau & Hedstrom, 1993; Hetherington & Orzek, 1989; Orzek, 1992).Past research has suggested that sexual orientation does affect career choice and career development; however, little research exists regarding the actual career development process of women who identify as lesbian (Shallenberger, 1998). Boatwright, Gilbert, Forrest, and Kretzenberger (1996) found that lesbians had often (a) reexperienced a second adolescence as they developed their lesbian identity, (b) experienced delays and disruptions in the career development process, and (c) experienced some career benefits from associating with other lesbians.…”
mentioning
confidence: 99%